Chernohirskyi Trail as a Brand of Ukrainian Hiking Tourism - Вишневський, Віктор Іванович (Київський національний університет імені Тараса Шевченка, 2020)
Aim: promotion of the walking route by the Chornohora Ridge of the Ukrainian Carpathians in the section from Hoverla to Pip Ivan mountain. Methods: observation, measurement, description, comparison, analysis, analogy, cartographic, statistical. Based on radar survey data SRTM and Global Mapper program it was created a three-dimensional image of the studied region. The SAS.Planet program was used to measure distances. Results: A three-dimensional image of the Ukrainian Carpathians was created using SRTM data. The main information about the highest Chornohirskyi Ridge in these mountains was presented. The route from Hoverla to Pip Ivan mountain is described. It is proposed to call it the Chernohirskyi Trail. Data on the height of the terrain at the beginning and end of the route are shown. A brief description of the tourist attractions on the trail is provided, including lakes Nesamovyte and Brebeneskul. Information on the meteorological and at the same time astronomical observatory "White Elephant", which was built on the eve of the Second World War was presented. Modern measures for its restoration are described, in particular as to installation of an automated meteorological station on its roof. Based on observations on nearby meteorological stations, the climatic conditions on the route were identified. Data about air temperature in January and in the warm period of the year are presented. The features of air temperature changes, depending on elevation, are established. Data on the amount of precipitation at existing meteorological stations in the mountains are provided. Information on the height of snow cover was presented. The features of snow formation and its disappearance in the southeastern part of the Ukrainian Carpathians are shown. Scientific novelty. The hiking route by the Chornohora Ridge of the Ukrainian Carpathians is substantiated as brand of Ukrainian hiking tourism. The expediency of traffic from Hoverla to Pip Ivan has been proved. It was found that at altitudes above 1000 m the decrease in air temperature in July is 0.40 C per 100 m altitude, in August – 0.30 C per 100 m. It is substantiated that the best time to travel along the Chornohirskyi Ridge is August. The significant distribution of snow cover on the Chornohirskyi Ridge, which is the highest within the Ukrainian Carpathians, is shown. Practical significance: popularization of tourism in the Ukrainian Carpathians, providing tourists with information to make travel more interesting and safe.

Мета: промоція пішохідного маршруту Чорногірським хребтом Українських Карпат на ділянці від Говерли до гори Піп Іван. Методика: спостереження, вимірювання, опис, порівняння, аналіз, аналогія, картографічний, статистичний. У праці для побудови об’ємного зображення досліджуваного регіону використано дані радарного знімання поверхні Землі SRTM, які опрацьовано з використанням програми Global Mapper. Для вимірювання відстаней використано програму SAS.Planet. Результати. З використанням даних SRTM побудовано об’ємне зображення Українських Карпат. Наведено основні відомості про найвищий у цих горах Чорногірський хребет. Описано маршрут від Говерли до гори Піп Іван. Запропоновано його назвати Чорногірською стежкою. Наведено дані щодо висоти місцевості на початку та наприкінці маршруту. Подано короткий опис наявних на стежці туристичних атракцій, зокрема озер Несамовите та Бребенескул. Наведено відомості про збудовану Польщею напередодні Другої світової війни метеорологічної і водночас астрономічної обсерваторії “Білий слон”. Описано сучасні заходи щодо її відновлення, зокрема встановлення на її даху автоматизованої метеорологічної станції. Спираючись на дані спостережень на найближчих метеостанціях, висвітлено кліматичні умови на маршруті. Подано дані про температуру повітря в січні та в теплий період року. Встановлено закономірності зміни температури повітря в залежності від висоти місцевості. Наведено дані щодо кількості опадів на наявних у горах метеостанціях. Подано відомості про висоту снігового покриву. Наведено дані щодо особливостей формування і сходження снігу в південно-східній частині Українських Карпат. Наукова новизна: обґрунтовано пішохідний маршрут Чорногірським хребтом Українських Карпат як бренд українського пішохідного туризму. Доведено доцільність руху від Говерли до г. Піп Іван. Встановлено, що на висотах понад 1000 м зниження температури повітря в липні становить 0,40 С на 100 м висоти, у серпні – 0,30 С на 100 м. Обґрунтовано, що найкращим часом для подорожей Чорногірським хребтом є серпень. Показано значне поширення снігового покриву на Чорногірському хребті, яке в межах Українських Карпат, є тут найбільшим. Практична значимість: популяризація туризму в Українських Карпатах, забезпечення туристів інформацією, яка дає змогу зробити подорожі цікавішими і безпечнішими.
Чорногірська стежка як бренд українського пішохідного туризму
Keywords: стежка; Чорногора; Говерла; Піп Іван; озеро; обсерваторія; температура повітря; тропа; Черногора; Поп Иван; обсерватория; температура воздуха; trail; Chornohora; Hoverla; Pip Ivan; lake; observatory; air temperature